The Impact of Cognition on Radar Technology - De Maio, Antonio; Farina, A. 1948-; Haykin, Simon S. 1931- (SciTech Publishing Inc., 2017)
The following topics are dealt with: cognitive radar; CFAR detection; receiver adaptation; cognitive optimization; transmitter-receiver pair; radar target tracking; MIMO radar; electronic warfare and synthetic aperture radar.